PERSPECTIVE ON FIRMS’ RESPONSES TO ECONOMIC CRISES - Isabirye, Joel (Annals of Spiru Haret University. Economic Series, 2021)
This paper analyzes how firms respond to emerging economic crises. A firm’s response to crisis is a mechanism for survival. It normally evolves out of the impact of the crisis, and it is linked to the strategic goals and operational objectives of the firm. Firms normally pursue one or more of three lines of responses to crises; retrenchment, investment and ambidextrous responses. Responses of firms to crisis are far from predictable or systematic and usually vary from firm to firm. They are predetermined by specific contexts of the firm’s existence. These contexts range from the firm’s size, ownership, sector of operation, history in business, country dynamics and resource capabilities. There is also a tendency for firms to move from one type of response to another during the course of the crisis. Retrenchment is the most preferred form of response, although investment responses tend to have long-term advantages. The study recommends that firms consider ambidextrous responses to realize the synchronized benefits of retrenchment and investment responses to crises. It is also recommended that studies on firms’ responses to crisis should examine firms on a case-to-case basis, identify the particularities of their responses.